RETRACTED ARTICLE: Valproic acid attenuates intercellular adhesion molecule-1 and E-selectin through a chemokine ligand 5 dependent mechanism and subarachnoid hemorrhage induced vasospasm in a rat model - Chih-Zen Chang; Shu-Chuan Wu; Chih-Lung Lin; Aij-Lie Kwan (BMC, 2015)
Abstract Background Up-regulation of regulated upon activation, normal T-cell expressed and secreted (RANTES/CCL5) and adhesion molecules is observed in the serum of animals following experimental subarachnoid hemorrhage (SAH). The present study was to examine the effect of valproic acid (VPA) on RANTES and alternation of adhesion molecules in this model. Methods A rodent SAH model was employed. Animals were randomly assigned into six groups. Basilar artery (BA) was harvested for intercellular adhesion molecule-1 (ICAM-1), vascular cell adhesion molecule-1 (VCAM-1), and E-selectin evaluation (western blotting) and RANTES (rt-PCR). 1 ng CCL5 recombinant protein intrathecal injection was performed in the VPA + SAH groups. (N = 5). Results Convoluted internal elastic lamina, distorted endothelial wall, and smooth muscle micro-necrosis was prominently observed in the SAH groups, which is absent in the VPA treatment and the healthy controls. Treatment with VPA dose-dependently reduced the ICAM-1, E-selectin and RANTES level, compared with the SAH group (p <0.01). The administration of CCL5 significantly increased CD45(+) glia and ICAM-1 level in the VPA treatment groups. Conclusion VPA exerts its anti-vasospastic effect through the dual effect of inhibiting RANTES expression and reduced adhesion molecules. Besides, VPA also decreased CD45(+) cells transmigrated to the vascular wall. The administration of CCL5 significantly reversed the inhibitory effect of this compound on CD45(+) monocytes, E-selectin, and ICAM-1 level. This study also lends credence to support this compound could attenuate SAH induced adhesion molecules and neuro-inflammation in a CCL5 dependent mechanism.